78.1k views
0 votes
*WORTH 6 POINTS*



Someone please help me. this is due tommorow.

*WORTH 6 POINTS* Someone please help me. this is due tommorow.-example-1

1 Answer

3 votes

Here are a few rules that apply to this expression:

  1. Powering a power:
    (x^m)^n=x^(m*n)
  2. Converting a negative exponent to a positive one:
    x^(-m)=(1)/(x^m);(1)/(x^(-m))=x^m

Firstly, solve the exponent:
(-6x)^(-2)=-6^(-2)x^(1*-2)=-6^(-2)x^(-2)

Next, convert the negative exponents:
-6^(-2)x^(-2)=-(1)/(6^2x^2)=-(1)/(36x^2)

Your final answer is -1/36x^2.

User Lukastymo
by
6.5k points